Control interno de las cuentas por pagar en la empresa BAMAREX S.A. del cantón Baba, periodo 2020-2021 - Ramos Tapia, Shayna Nicole (2023)
BAMAREX S.A. is a banana producer and exporter located in the Baba canton and is required to keep accounting records according to the internal tax regime law during the period 2020-2021. The research focuses on the inconsistencies detected in the accounts payable of BAMAREX S.A. during the period 2020-2021, indicating a weakness in the company's internal control system of accounts payable. Internal control of accounts payable is crucial to ensure transparency and integrity in the company's financial operations and reduce financial errors and fraud risks. The main objective of the research is to analyze the internal control of accounts payable in BAMAREX S.A. during the period 2020-2021, to identify possible inconsistencies that may be affecting their financial management and reputation in the market. The importance of this study lies in the fact that internal control of accounts payable is essential to ensure that financial obligations are fulfilled properly and in a timely manner. This paper focuses on descriptive and analytical research of the internal control of accounts payable in the company. To gather relevant information, a combination of direct observation and interviews with the company's accountant is used. The methodology employed provides a clear view of the current situation of internal control in the accounts payable of the company.